PEMULIAAN KETAHANAN TANAMAN WIJEN TERHADAP PENYAKIT BUSUK PANGKAL BATANG (Phytophthora sp.) - Sri Adikadarsih; Ruly Hamida (Universitas Islam Madura, 2015)
One of the obstacles in the sesame plant breeding is a disease. Often to the detriment of potential disease is stem root symptoms and causative pathogen is the fungus Phytophthora sp. Losses caused by these pathogens can reach 50%, as it includes a soil borne disease and can cause a fall in the seed sprouts, thus potentially causing harm. The challenge remains to this day breeding research sesame resistance to Phytophthora sp. conducted in Indonesia and abroad is still very little. Until now, Phytophthora species on sesame plants yet further determination. Testing of the phytoalexin in sesame plants as active resistance mecanism sesame plant has not been done in depth, as well as the action of the sesame plant resistance genes against Phytophthora has not been much discussed.